Seasonal Variations of Green Seaweeds (Chlorophyta) from the Undi Coastal Area of Ratnagiri, Maharashtra - ADSUL, A D; SHELAR, P S; SHINDE, M M; SHELKE, A A; INDULKAR, S T; SAWANT, M S (Journal of the Indian Society of Coastal Agricultural Research, 2019)
In the present study, monthly and seasonal variations in abundance of green seaweeds from the coastal region of Undi, Ratnagiri district along the west coast of Maharashtra were investigated. Stratified random sampling was carried out during monthly lowest tides along the exposed intertidal rocky shore area. For the estimation of percentage coverage of seaweeds, photo-quadrate method was employed. For the quantitative estimation of green seaweeds, collected samples from the quadrate were sorted out separately as per species and wet/ fresh weights were taken for density and biomass estimation of respective seaweed species. A total of ten green seaweeds were found in the rocky shore of UndiÂ viz.,Â Bryopsis plumosa,Â Chaetomorpha antennina,Â Chaetomorpha crassa,Â Caulerpa racemosa,Â Caulerpa peltata,Â Caulerpa taxifolia,Â Caulerpa sertularioides,Â Ulva lactuca,Â Ulva fasciataÂ andÂ Valonia utricularis. In the study area, most of the green seaweeds were recorded with maximum abundance during pre-monsoon and post-monsoon seasons, while in monsoon season the abundance of most of the green seaweeds remarkably declined. Unlike other seaweeds, maximum biomass of seaweeds,Â Bryopsis plumosaÂ andÂ Ulva lactucaÂ was recorded during monsoon season. Among the green seaweeds, species likeÂ Caulerpa peltata,Â Ulva lactucaÂ andÂ Caulerpa taxifoliaÂ were recorded throughout the year. During whole monsoon season, among green seaweeds,Â Ulva fasciataÂ was totally absent while during late pre-monsoon, species likeÂ Bryopsis plumosa,Â Chaetomorpha crassa,Â Caulerpa racemosaÂ andÂ Valonia utricularisÂ were totally absent. The maximum biomass ofÂ Caulerpa peltataÂ was recorded in the month of February 2018 in pre-monsoon period. The water pH showed highly significant positive correlation with abundance of green seaweeds,Â Caulerpa peltataÂ andÂ Ulva fasciata. Green seaweeds were found to be abundant along the coastal margin of Ratnagiri, with species specific seasonal variations in their abundance.